Rhizophagus atticus Tozer, 1968 in France: synonymy with R. diaboli Dodelin, 2021, distribution and ecology (Coleoptera: Monotomidae) - Barnouin, Thomas; Vincent, Alexis; Soldati, Fabien (Zootaxa, 2025)
As part of the pinewood nematode monitoring program implemented in 2021 and 2022, we collected abundant specimens of Rhizophagus diaboli Dodelin, 2021 (Coleoptera, Monotomidae), a species recently described from France within the subgenus Eurhizophagus Méquignon. Comparison of the 359 individuals with 1,886 specimens of R. depressus (Fabricius) caught in the same trapping system confirmed the existence of two distinct taxa. On the other hand, comparison with 3 type specimens of R. atticus Tozer, 1968, including study of aedeagi, showed that there were no morphological differences. A new synonymy is therefore established: Rhizophagus atticus Tozer, 1968 = Rhizophagus diaboli Dodelin, 2021, syn. nov. An updated identification key to species for this subgenus and photographs of type specimens are presented. Its distribution in France, which currently covers 43 communes and 30 administrative departments, is illustrated and commented. Its phenology and altitudinal distribution are analyzed and compared with those of R. depressus. Rhizophagus atticus appears to be a species associated with low-altitude pine forests, with highest activity in August.